Kajian struktural pada novel Al-Ajnihah Al-Mutakatstsirah karya Kahlil Gibran: Sebuah analisis - Ammar, Zaqhlul (Maliki Interdisciplinary Journal, 2024)
This article aims to analyze the narrative structure and structural elements in Kahlil Gibran's novel "Al-Ajnihah Al-Mutakassirah". The object of this study is the novel itself, known for its themes of love, sacrifice, and freedom. The research employs a qualitative descriptive method to provide a thorough and detailed overview of the structural elements in the novel. The approach used in this analysis is Robert Stanton's structuralism theory, which includes an analysis of plot, setting, characters and characterization, point of view, and symbolism in the story. The analysis results indicate that the narrative structure constructed by Gibran is highly effective in conveying the main themes of the novel. The plot, consisting of exposition, conflict, climax, and resolution, helps readers to follow the emotional and psychological journey of the main character, Kahlil, clearly. Furthermore, the characters in the novel are developed through deep characterization, revealing their psychological and moral complexities. Symbolism is also used effectively to enrich the story and deepen readers' understanding of the meanings of love, sacrifice, and freedom. The findings of this research emphasize the importance of a structural approach in analyzing literary works, enabling a more comprehensive and profound understanding of the text. Thus, this article makes a significant contribution to literary studies, particularly in understanding how structural elements contribute to shaping narrative and themes in the novel "Al-Ajnihah Al-Mutakassirah".